A study of fracture toughness of heavy-weight concrete and foam concrete reinforced by polypropylene fibre for road construction - Солодкий, Сергій Йосипович; Каганов, Вадим Оскарович; Горніковська, Ірина Богданівна; Турба, Юрій Васильович (Eastern-European Journal of Enterprise Technologies, 2015)
The study explores fracture toughness of heavy-weight concrete and foam concrete solidified by an autoclave-free method and reinforced vs. non-reinforced with polypropylene fibres. The research was conducted by the criteria of fracture mechanics to determine strength and deformation characteristics as well as power and energy features of fracture toughness of the considered concretes. It has been discovered that addition of polypropylene fibreto the composition of heavy-weight concrete and foam concrete mainly affects the supercritical phase of deterioration: the fibre inhibited fracture of the samples once there had appeared a backbone crack (from the moment when the maximum breaking load had already been applied) until its complete defragmentation. The indicator characterizing this effect—the specific energy load used for static destruction, GF—was higher in all series of dispersed concrete reinforcement, which was quite different in the case of non-reinforced concrete and foam concrete. It proved to be the most effective additive in heavy-weight concrete and porous concrete with a density of 700 kg/m3 (respectively, the indices were 1.5 and 1.8 times higher than in the case of non-reinforced concrete). Besides, adding polypropylene fibre increases, by 22% on average,the tensile strength of concrete while bending it. Hence, formation and development of cracks are inhibited by polypropylene fibres, which can be observed in an increase of all indicators of strength and deformability of the studied concretes as well as of power and energy features of fracture toughness.